â€œWell; I thinkâ€¦â€, the Dominant Hedges Uttered by Males in Daily Communication: A Sociolinguistic Study - Nadianto Nugroho Rizky Abadi; Lina Purwaning Hartanti; Setiawan Setiawan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
Hedges are linguistics features that were previously considered by some researchers as the characterization of women's speech to show hesitation and uncertainty of the speech regarding the character of discussion and the sensitivity of the questions. However, this claim was remain debatable by another researcher since the use of hedges cannot be correlated to any specific gender. This study was conducted to reveal the use of hedges can also be employed by males in an informal daily conversation, discussing lights topic and questions that often appear. The conducted study was supported by the transcription from the recorded online meeting with males native and non-native English speakers. The transcribed recorded online meeting was useful to examine the hedges as the participants' expressions in the discussion. The results of the study showed that males also utilized hedges in an informal discussion, and the most frequent one is verbal filler will. The hedges uttered by both males native and non-native were various such as to give them chance to think, to reduce the impact delivered, self-disclosure, and appraise someone's idea. The findings also found that the use of hedges by males in casual daily conversation is normal, in regard to saving the speaker's name toward the interlocutor when discussing a sensitive topic or answering a sensitive question.